2014
DOI: 10.1177/0148607114549769
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Nutrition Supplements on Hospital Outcomes in Pediatric Patients

Abstract: ONS use was associated with lower LOS and episode cost among pediatric inpatients. ONS use in hospitalized pediatric patients may provide a cost-effective, evidence-based approach to improving pediatric hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The notable lack of primary cost analyses in adults and the total absence of identifiable studies in children from the literature search weaken the generalizability of the findings, although one retrospective analysis based on observational data in children has been published since our literature search [46], which suggests that ONS reduces length of hospital stay by 14.8% and costs by 9.7%.…”
Section: Discussionmentioning
confidence: 89%
“…The notable lack of primary cost analyses in adults and the total absence of identifiable studies in children from the literature search weaken the generalizability of the findings, although one retrospective analysis based on observational data in children has been published since our literature search [46], which suggests that ONS reduces length of hospital stay by 14.8% and costs by 9.7%.…”
Section: Discussionmentioning
confidence: 89%
“…A retrospective, instrumented analysis of 555,348 hospitalized American children (2-8 years old) showed that ONS prescriptions given to 1.09% of the patients reduced average LoS by 14.8% (6.4 days vs 7.5 days) and were associated with a 9.7% decrease in hospital costs (US$16,552 vs US$18,320; US$1,768 [95% CI, US$1,924-US$1,612]) (26).…”
Section: Depletion Of Body Muscle and Fat Tissues Including Intra-mentioning
confidence: 99%
“…An excellent review of QI methods may be found in the The Healthcare Quality Book by Joshi et al 37 Multiple studies indicate such work can drastically improve patient outcomes and reduce health care costs. 25,[38][39][40]…”
Section: Role For Pediatric Hospitalistsmentioning
confidence: 99%